An All-Solid Dispersion-Compensating Photonic Crystal Fiber Based on Mode Coupling Mechanism in Dual-Concentric Core - Liu, Zhaolun; Zhang, Chunlan; Qu, Yuwei (International Journal of Optics, 2020)
An all-solid dispersion-compensating photonic crystal fiber based on mode coupling mechanism in dual-concentric core has been proposed. The mode coupling characteristics, dispersion, confinement loss of the fiber, and the influence on dispersion of some structure parameters are simulated by full-vector finite element method. By using the relationship between phase matching wavelengths and coupling strength with the change of fiber microstructure parameters, an all-solid dual-concentric-core dispersion-compensating photonic crystal fiber is presented. The structure parameters on dispersion characteristic are investigated. The results demonstrate that the proposed fiber has a large negative dispersion value 8465 ps/(nm·km) at 1550 nm. The effective mode area and the splicing loss to the standard single mode fiber are 12.8 μm2 and 1.89 dB at 1550 nm, respectively. At 1550 nm, the confinement loss is less than 1 × 10−3 dB/km and the bending loss with 2 cm bending diameter is less than 1 × 10−2 dB/km.